2023
DOI: 10.3390/biom13020376
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Phytocannabinoid Cannabigerol for Multiple Sclerosis: Modulation of Microglial Activation In Vitro and In Vivo

Abstract: Multiple sclerosis (MS) is a widespread chronic neuroinflammatory and neurodegenerative disease. Microglia play a crucial role in the pathogenesis of MS via the release of cytokines and reactive oxygen species, e.g., nitric oxide. Research involving the role of phytocannabinoids in neuroinflammation is currently receiving much attention. Cannabigerol is a main phytocannabinoid, which has attracted significant pharmacological interest due to its non-psychotropic nature. In this research, we studied the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…CBG is marketed as a dietary supplement [ 37 ], and in vivo studies have been performed in rodents showing that CBG is well tolerated and exerts anti-inflammatory and neuroprotective activities [ 36 , 37 , 56 , 57 , 58 ]. Because CBG also has antimicrobial activities, especially against Gram-positive bacteria including S. aureus [ 29 , 30 , 40 , 41 ], its efficacy was investigated when incorporated into a slow-release varnish (SRV) applied on a biodegradable Vicryl mesh.…”
Section: Discussionmentioning
confidence: 99%
“…CBG is marketed as a dietary supplement [ 37 ], and in vivo studies have been performed in rodents showing that CBG is well tolerated and exerts anti-inflammatory and neuroprotective activities [ 36 , 37 , 56 , 57 , 58 ]. Because CBG also has antimicrobial activities, especially against Gram-positive bacteria including S. aureus [ 29 , 30 , 40 , 41 ], its efficacy was investigated when incorporated into a slow-release varnish (SRV) applied on a biodegradable Vicryl mesh.…”
Section: Discussionmentioning
confidence: 99%
“…However, other cannabinoids have not been extensively studied. Future research could focus on clinical trials to investigate the therapeutic potential of these lesser-known cannabinoids and their derivatives, which have proven in vitro or in vivo biological activity, such as the following: THCV-antiepileptic activity [347], potential against Parkinson's disease [348,349], antipsychotic effects [350], CBG-anticonvulsant activity [351], counteract neuroinflammation [352], neuroprotective in Huntington's disease [202], in multiple sclerosis [353], CBG derivatives-anti-inflammatory in multiple sclerosis [354], in amyotrophic lateral sclerosis [355], neuroprotective potential in Huntington's disease [356], in Parkinson's disease [357][358][359], CBC-promotes neural stem/progenitor cells viability [360], induces neuronal differentiation in NSC-34 Cells [361], antinociceptive activity [362], anti-inflammatory [363], CBN-neuroprotective activity [167], antiseizure potential [364].…”
Section: Clinical Trials With Specific Cannabinoidsmentioning
confidence: 99%
“…CBG is known to exhibit anti-inflammatory and antioxidant properties [115]. In relation to neurological diseases, it has been observed that in models of multiple sclerosis CBG attenuated the microglial production of nitric oxide and TNF-α levels are significantly reduced, restoring the neuronal loss [116,117]. VCE-003, a derivative of CBG quinone, has also demonstrated protective activity against neurodegeneration and neuroinflammation in various experimental models of Huntington's disease and Parkinson's disease [118][119][120][121].…”
Section: Role Of Cannabis Compounds In Neurological and Systemic Infl...mentioning
confidence: 99%